Cartoons and the Egyptian Transition: A Qualitative Analysis of Egyptian Newspapers - Sara S. Elmaghraby (Global Media Journal: German Edition, 2014)
Since the Egyptian revolution of 25 January, cartoonists have depicted the transition taking place in this country in several ways. This study aims to analyze the cartoons drawn about this transition period in Egypt in seven different Egyptian newspapers. This is done through a qualitative analysis of 80 cartoons published between 28 June and 4 July 2013, as this period saw the ousting of elected president Mohamed Morsi by the military general Abdel Fattah Al-Sisi. The study observes the different depiction of various topics, actors and visual frames used by the seven newspapers during the analyzed period, in accordance with their particular viewpoint of the transition in Egypt.